Geochronology of the felsic rocks in Orijärvi, southern Finland – implications for stratigraphy - Elisa Toivanen; Teemu Vehkamäki; Markku Väisänen; Jaakko Kara; Hugh O’Brien (Estonian Journal of Earth Sciences)
The Orijärvi area within the Paleoproterozoic Uusimaa belt contains volcanic and minor sedimentary formations, providing valuable insights into the oldest Svecofennian crust in southern Finland. Previously, felsic volcanic rocks from the Orijärvi, Kisko and Toija formations have been dated at 1895 ± 3, 1878 ± 4 and 1878 ± 4 Ma, respectively. In the present study, the Sorvasto sample from the southern boundary of the Kisko formation yields a zircon age of 1885 ± 5 Ma and a titanite age of 1800 ± 15 Ma. The zircon age falls within the interval between previously obtained age determinations and is coeval with the common Svecofennian crustal growth stage. The Kavasto sample from the western part of the area yields a zircon age of 1878 ± 6 Ma and a titanite age of 1796 ± 4 Ma. The zircon age corresponds to those obtained for similar rock types in the Toija and Ahdisto formations. Picritic interlayers occur within all these successions and are here interpreted as belonging to the same Toija formation. We tentatively infer that the Toija and Salittu formations, together with the overlying sedimentary rocks, can be traced to the West Uusimaa area in the east and the Turku area in the west. The titanite ages near 1.80 Ga reflect cooling or reheating events.